A simple discharge criteria for transfer of patients from intermediate care to general care: a prospective observational study - Syed Ahsan Ali; Misbah Fazlani; Tazein Amber; Safia Awan (Journal of the Pakistan Medical Association, 2022)
Objective: To develop and apply a simple criterion for transfer of patients from intermediate care to general care. Method: The prospective study was conducted in the intermediate care units of Aga Khan University Hospital, Karachi, from July to December 2018. A discharge criterion for transfer of patients from intermediate care to general care was developed according to which patients with vital signs and Glasgow Coma Scale score within a preset range were considered stable enough for transfer from intermediate care to general care. After labelling the patients on the basis of the criterion, it was determined on the following day which patients remained stable enough for transferred to general care, and which patients became unstable. Data was analysed using SPSS 19. Results: Of the 49 patients with mean age 63.0±16.9 years, 28(57.1%) were males. Overall, 43(87.7%) patients remained stable on the next day. Of them, 33(67.3%) patients were transferred out from intermediate care on the subsequent day, while 8(16.3%) were not transferred out due to primary physician’s decision, 1(2%) due to heparin infusion, and 1(2%) due to family request. The condition of the remaining 6(12%) patients deteriorated. Conclusions: A simple discharge criterion is proposed for intermediate care solely based on clinical parameters. Significant majority of the patients remained stable and were transferred out of intermediate care. Key Words: Criteria, Discharge, Intermediate care, Simple, Throughput.